SCOPE AND APPROACH TO SUPERVISION IN THE WORLD OF EDUCATION - Idris, Ahmad; Firdaus, Arif Faqih; Marfu, Asep; Supardi, Supardi; Gunawan, Agus (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
Education is a process that occurs between students and teachers, has a very crucial function and acts as a valuable resource in human life. To achieve a higher quality of education. it requires teaching staff who have high skills and levels of professionalism in their respective fields. In general, aspects of educational supervision are divided into two main categories, namely academic supervision and administrative supervision. Academic supervision is related to development efforts aimed at improving the quality of teaching in the classroom, with a primary focus on teacher behavior while teaching and the interactions that occur during the educational process. This study aims to understand the scope and methods applied in educational supervision. The methodology used in this study is qualitative research. This type of research is a literature study that aims to collect information from various books or existing sources. It can be said that the scope of supervision is in the fields of student affairs, infrastructure, administration, student affairs, and also in the field of finance. Then the approach used by the supervisor is a direct approach, an indirect approach. and a collaborative approach between the direct and indirect approaches. With a deep understanding of the scope and methods of supervision in educational institutions, institutions can be directed to achieve better educational goals.